1988
DOI: 10.1055/s-2008-1026525
|View full text |Cite
|
Sign up to set email alerts
|

Die spontane Zökumperforation nach Sectio caesarea

Abstract: There is a certain risk of paralytic distension of the bowel, especially of the coecum, during the initial post-operative days following caesarean section. As can be seen from the overview presented, the possible result is spontaneous perforation of the coecum, which frequently has lethal consequences. Early differential diagnostic consideration for a mother exhibiting early warning post-caesarean symptoms can be life saving. We would recommend as prophylaxis early bowel stimulation with a laxative already on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Strecker et al reported that the association of Ogilvie's syndrome and vaginal delivery may be due to declining estrogen levels in post-partum period. 4 The mechanism of action is the loss of tone in parasympathetic nerves in S2 to S4 resulting in atonic distal colon and pseudo-obstruction. Abdominal distension is the most common symptom.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strecker et al reported that the association of Ogilvie's syndrome and vaginal delivery may be due to declining estrogen levels in post-partum period. 4 The mechanism of action is the loss of tone in parasympathetic nerves in S2 to S4 resulting in atonic distal colon and pseudo-obstruction. Abdominal distension is the most common symptom.…”
Section: Discussionmentioning
confidence: 99%
“…5 Keswani et al reported that a cecal diameter of 9 cm or more is the only definitive sign of imminent perforation. 4 Stephenson et al reported that use of pro-kinetic drugs like neostigmine may be beneficial in selected cases. 6…”
Section: Discussionmentioning
confidence: 99%
“…Bed rest and abnormal electrolytes are also listed as factors associated with the development of the syndrome [4], and Strecker et al reported that the association between Ogilvie's syndrome and vaginal delivery may be due to the declining serum oestrogen levels in the post-partum period [5]. In the only other reported case of Ogilvie's syndrome following normal vaginal delivery in the English literature, the histological findings of the caecum after right hemicolectomy showed no specific pathology [3].…”
Section: Discussionmentioning
confidence: 99%
“…Stephenson et al have shown that the use of prokinetic, parasympathomimetic drugs such as neostigmine can be successful in the management of Ogilvie's syndrome, although the benefit in cases of idiopathic Ogilvie's syndrome is not certain [7]. With regard to post-partum patients, Strecker et al support the use of laxatives in the post-partum period and stress the importance of early diagnosis [5]. …”
Section: Discussionmentioning
confidence: 99%